The sharpness of the images in metallography - A. G. Anisovich (Литьë и металлургия)
The article presents the issues of sharpness of images of the structure of materials in metallographic studies. The use of the concept of depth of field to obtain images of the structure of various objects – fractures, microsection polished specimen, optically transparent materials is illustrated. The errors of focusing on the sharpness for metal specimens are considered; it is shown that in the case of inclined arrangement of the specimen, the zone of sharp image is a strip with parallel boundaries formed by a fuzzy visible structure. Particularities of focusing out-of-flatness samples and replicas are shown. It is noted that the location of the areas of the non-sharply visible structure in the image is the result of external influence. The possibilities of varying sharpness for the quantitative analysis of austenite grain, as well as the visualization of dendritic structures are demonstrated.